PERAN IBU RUMAH TANGGA DALAM PENGOLAHAN MINYAK KELAPA DI DESA LAHAJI KECAMATAN NAPANO KUSAMBI KABUPATEN MUNA BARAT - Hasmi Hasmi; La Nalefo; Laode kasno Arif (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
In contexts characterized by constrained family economic circumstances, domestic workers often engage in coconut oil processing as a strategy to augment family income. The objective of this study is to ascertain the role of housewives in the coconut oil processing industry in Lahaji Village, Napano Kusambi District, West Muna Regency. The population of this study comprised ten coconut oil processors from Lahaji Village. The research sample was determined using census techniques. The focal point of this study is the role of housewives in the processing of coconut oil. The data presented herein was collected through a combination of observation, documentation, and interviews conducted using a structured interview technique. The data were analyzed using a qualitative descriptive method that was processed in three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that housewives in Lahaji Village play a dominant role in the entire coconut oil processing chain, particularly in the processing, packaging, and marketing stages, with active involvement from determining the amount of raw materials, grating, pressing, cooking coconut milk, to filling packaging and selling. However, during the raw material preparation stage, such as collecting and transporting coconuts, their role tends to be passive, reflecting a gender-based division of labor. The active, passive, and participatory roles of housewives at each stage of coconut oil production reveal the potential for increasing women's involvement in technical aspects that have traditionally been dominated by men.